PENGARUH PUPUK ORGANIK DAN DOLOMIT PADA LAHAN PANTAI TERHADAP PERTUMBUHAN DAN HASIL KEDELAI - Feri Anitasari; Rahayu Sarwitri; Agus Suprapto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Experiment on the assessment results of Grobogan soybean varieties with organic fertilizer and dolomite in coastal land held in April-July 2013. The site was in the village of Dusun Karang Jiat Pasar Anom District Purworejo with a altitude of 5 m where the soil type was regosol and soil pH was 5,5. The research method used was factorial (4x4) which are arranged in complete dose randomized block design with three replications. The first factor was Shisako+ with fertilizer: 3; 3,5;4;4,5 ton/ha. The second factor was of dose of dolomite: 2;2,5;3;3,5 ton/ha. The result showed that the use organic fertilizer until 4,5 ton/ha showed relatively similar responses to plant height, pod dry weight, seed dry weight and dry weight of soybean stalk. Applying dolomite until 3,5 ton / ha showed relatively similar responses to plant height, pod dry weight, dry seed weight and dry weight of soybean stalk.Keywords: coastal land, dolomite, organic fertilizer, soybean